If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(-6 + 6k) = 87 3 + (-6 * -2 + 6k * -2) = 87 3 + (12 + -12k) = 87 Combine like terms: 3 + 12 = 15 15 + -12k = 87 Solving 15 + -12k = 87 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -12k = 87 + -15 Combine like terms: 15 + -15 = 0 0 + -12k = 87 + -15 -12k = 87 + -15 Combine like terms: 87 + -15 = 72 -12k = 72 Divide each side by '-12'. k = -6 Simplifying k = -6
| 3(1-2y)+y=-3+1 | | 6s=-54 | | 5n^2-20n-25=0 | | 9a+9=3a-15 | | 2t^2+-3=0 | | -7x=5x^2-6 | | -3(3b+2)+(10b-2)=0 | | 4(5n-6)+4n=-96 | | 4x-(2x+13)= | | c-8=12 | | 2*ln(x-3)-1=6 | | x+x+2=18 | | x^2-78x-15=0 | | x^2-78-15=0 | | u=x^2-6x+11 | | y=x^2+6x+11 | | x^2+22x+72=0 | | a+15=34 | | 5x+1=4.5 | | 5.8q-3.7-5.3q=0.5q-2.9 | | x^2+x=x-3 | | 76=6(4-4b)-2b | | -2(3n-1)+2n=6-2 | | 8(a+3)=2[2a-(6-a)] | | 5=7x-23 | | 2x-18=32 | | 3x^2-2x+6=9 | | 3x^2-23x+30= | | .5x(x-3)=65 | | 12X=3X^2-96 | | 5.8q-3.7-5.3=0.5q-2.9 | | -1.2=y-1 |